Konfrontasi Malaysia Indonesia - Nik Anuar Nik Mahmud (Bangi : Penerbit Universiti Kebangsaan Malaysia, 2000)
History of the Malaysia-Indonesia conflict
Bibliografi : p. 247 - 250
Buku bacaan asas fakulti
In Malaysia
Keywords: Malaysia -- Foreign relations -- Indonesia; Malaysia -- History; Indonesia -- History